Representing Peace? The EU's Temporal Selves and its Statebuilding - CEBECİ, EMİNE MÜNEVVER (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
This article provides a poststructuralist analysis of the interplay among the EU's three temporal selves, elucidating how the ideal representations of the EU's past and future selves legitimize its statebuilding activities, particularly in cases of contested statehood in its neighbourhood, and reproduce the ideal European self today. The major argument of the article is that the discourse of successful peaceful European integration (employed to construct the EU's past self) and the discourse on the EU's normative aspirations about state-/peace building (employed to construct its future self) help constitute its present identity as representing peace - and, thus, as ideal - and legitimize its statebuilding practices. The article takes the ideal constructions of the EU's past, present and future selves as spatio-temporal practices because they serve the continuous production and reproduction of the boundaries between a peaceful Europe and its conflictual others, which primarily refers to a geographical/geopolitical othering exercise.
Keywords: NORMATIVE POWER; LIBERAL PEACE; LAW MISSION; EUROPE; GOVERNMENTALITY; GOVERNANCE; SECURITY; MOLDOVA; POLICY; RULE